2019
DOI: 10.3390/s19132892
|View full text |Cite
|
Sign up to set email alerts
|

3D Tdoa Problem Solution with Four Receiving Nodes

Abstract: Time difference of arrival (TDOA) positioning methods have experienced growing importance over the last few years due to their multiple applications in local positioning systems (LPSs). While five sensors are needed to determine an unequivocal three-dimensional position, systems with four nodes present two different solutions that cannot be discarded according to mathematical standards. In this paper, a new methodology to solve the 3D TDOA problems in a sensor network with four beacons is proposed. A confidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 19 publications
0
35
0
Order By: Relevance
“…This means that in these sensor deployments a sensor fault will cause the unavailability of TOA architectures with 4 sensors and TDOA architectures with 5 sensors. However, our finding in [13] has determined that an unequivocal solution for these systems with a possible sensor failure -3 sensors in TOA and 4 sensors in TDOA-can be achieved under an optimized node localization. As a consequence, an optimized sensor distribution can guarantee the availability of the system in sensor failure conditions through the consideration of a methodology to enhance the system properties in these situations.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…This means that in these sensor deployments a sensor fault will cause the unavailability of TOA architectures with 4 sensors and TDOA architectures with 5 sensors. However, our finding in [13] has determined that an unequivocal solution for these systems with a possible sensor failure -3 sensors in TOA and 4 sensors in TDOA-can be achieved under an optimized node localization. As a consequence, an optimized sensor distribution can guarantee the availability of the system in sensor failure conditions through the consideration of a methodology to enhance the system properties in these situations.…”
Section: Introductionmentioning
confidence: 94%
“…As a consequence, the position determination by means of iterative methods provides a unique solution that it might not match with the real target location. Nevertheless, we have shown in [13] that the optimal solution can be achieved by maximizing the radius of convergence of the initial iteration point which forces the iterative method to converge to the real solution in a high confidence interval. It has been demonstrated that this fact coincides with the maximization of the distance between the two possible solutions in LPS.…”
Section: Taylor-based Positioning Algorithm In Time Difference Of Arrmentioning
confidence: 99%
See 2 more Smart Citations
“…With the rise of the fifth-generation communication system (5G), Internet of things, automatic pilot and unmanned aerial vehicle, localization continues to receive great attention [1][2][3][4]. Based on different type of measurements, the common localization methods estimate the source position using time of arrival (TOA), time difference of arrival (TDOA), angle of arrival (AOA), Doppler frequency, Fingerprint and received signal strength (RSS) [5][6][7][8][9][10][11][12][13]. To improving the accuracy further, a series of hybrid method is developed by combining several kinds of measurements [14][15][16].…”
Section: Introductionmentioning
confidence: 99%